Faktor-Faktor Yang Berhubungan Dengan Siklus Menstruasi Pada Mahasiswi S1 Keperawatan Di Universitas Harapan Bangsa - Amalia, Aninda Novra; Haniyah, Siti; Apriliyani, Ita (Peneliti.net, 2025)
The menstrual cycle is the menstrual cycle that occurs in women every month, starting from the first day of menstruation to the first day of menstruation in the following month. Risk factors for menstrual cycle disorders are physical activity, stress levels, body mass index (BMI) and anemia. The purpose of this study was to determine the factors associated with the menstrual cycle in undergraduate nursing students at Harapan Bangsa University. The design of this study was cross-sectional. The sample technique used was total sampling with a total sample size of 85 respondents. The variables studied were stress level, physical activity, and Body Mass Index (BMI). Data analysis used univariate and bivariate analysis with spearmank ranks correlation statistical test. Data were collected by filling out the International Physical Activity Questionnaire- Short Form (IPAQ-SF) questionnaire to measure physical activity levels, Depression Anxiety Stress Scales (DASS 42) to measure stress levels and height and weight to calculate Body Mass Index (BMI). The results of this study showed that there was no relationship between stress level and menstrual cycle with p-value 0.299 (>0.05), no relationship between physical activity and menstrual cycle with p-value 0.954 (>0.05), and no relationship between Body Mass Index (BMI) and menstrual cycle with p-value 0.722 (>0.05). The conclusion of this study is that stress level, physical activity and Body Mass Index (BMI) are not associated with menstrual cycle.